Work Ethics and Employee Job Satisfaction in Nepalese Commercial Banks of Butwal Sub-Metropolitan City (The Lumbini Journal of Business and Economics, 2025)
Purpose: The paper examines the impact of Care, ethical code, Regulations, Instruments, Independence, Hard Work and Work as goal on job satisfaction in Commercial Banks. Methods: The study adopted a descriptive and causal-comparative research design, utilizing statistical measures such as Mean, Standard Deviation, Correlation, and Regression for data analysis. Data were collected from 240 commercial bank employees using a convenience sampling method. Participants provided confidential responses to a detailed questionnaire, rating their perceptions on a clear 7-point Likert scale. Results: The results reveal that care, regulations, independence, hard work and work as goal have significant impact on job satisfaction. Female employees have better opinion with regard to care on the other hand, employees of all age groups have similar opinion on work ethics and job satisfaction.Conclusion: This study concludes that work as goal is the most influencing factors of work ethics on job satisfaction. So, employees who set goals in professional life tend to get higher job satisfaction